Chinese EFL University Students’ Self-Efficacy for Online Self-Regulated Learning: Dynamic Features and Influencing Factors - Xu, Qi; Wu, Jin; Peng, Hongying (Frontiers in Psychology, 2022)
Self-efficacy is crucial for successful self-regulated learning, particularly in an online environment, yet research on self-efficacy for online self-regulated learning has received relatively little empirical attention in the language education domain. In this study, we investigated the dynamic features of English as a Foreign Language (EFL) university students’ self-efficacy for self-regulated learning (SESRL) in the online environment, and explored the influencing factors on SESRL. Multiple sources of data (questionnaires, reflective journals, and semi-structured interviews) over a period of one semester were collected, analysed, and triangulated. Our results demonstrated that most students displayed a relatively constant and high self-efficacy for self-regulated online learning, and that a few students also experienced an increased or decreased self-efficacy for self-regulated learning. Thematic analysis further revealed a variety of task-, learner-, course-, and technology-level factors contributing to learners’ self-efficacy beliefs for self-regulated online learning. Our findings thus offer pedagogical implications for self-regulated foreign language learning in an online context.